The effects of band and broadcast fertilizer application on soil fertility and growth of aerobic rice. – A case study using MRIA1 planting materials / Muhammad Afifi Mohamed Akbar - Mohamed Akbar, Muhammad Afifi (Faculty of Plantation and Agrotechnology, 2017)
A different types of fertilizer application used in this projects was tested to get the responses growth of aerobic rice, variety MRIA1, and effects on soil fertility. Broadcasting application means that fertilizer is spread uniformly over the soil surface area which are target to be treated while banding placement is a mechanical technique in order to open a furrow or trench and the fertilizer is applied in a band below the soil surface. This study was using randomized complete block design (RCBD) with four treatments, four replications in four block at share farm UiTM Jasin and the soil analysis methods used are standard soil pH and wet digestion methods. There is no significant difference (p=0.980) between fertilizer application to the growth of aerobic rice and the concentration of phosphorus for before (p=0.429) and after manuring (p=0.487) while there is significant difference (p=0.000001) between fertilizer application to the concentration of potassium before manuring and no significant differences (p=0.436) after applying manuring. Based on this study, the mean of potassium concentration decreases after manuring, at least zero miligram per kilogram, thus, in order to reduce fixation and leaching of phosphorus and potassium in soil, soil need to apply liming before planting.